Experiences of social workers regarding managing workload during COVID-19 pandemic: A study at the Department of Social Development in Roodepoort - Mambabada, Tshiwela Portia (University of the Witwatersrand, Johannesburg, 2024)
The aim of this study was to explore experiences of the Department of Social Development (DSD) social workers when managing their workload during the COVID-19 pandemic. This is a qualitative study that employed exploratory case study research design to understand the experiences of participants in their everyday life within their workplace. The researcher utilised a non-probability purposive sampling procedure to select participants. Fifteen (15) participants were recruited from Roodepoort’s DSD in South Africa. The researcher used a semi-structured interview schedule as the data collection tool. Data was collected on one-on-one basis, face-to- face with participants. The researcher was interested in utilising a thematic analysis to analyse the collected data. The study offers insights into how social workers’ workload at DSD changed as a result of the COVID-19 pandemic. The insights are used to make recommendations for future disaster plans to support social workers and the clients that they serve within DSD. Fundings show that Roodepoort DSD social workers faced higher caseload in foster care. This was as a result of a shortage of social workers and limited resources during the COVID-19 pandemic. These social workers also faced changes that were brought about by the pandemic, such as the shortage of personal protective equipment and they had to adopt hybrid work to provide services to clients virtually. They experienced poor mental health due to increased workload, stress, and burnout. Their coping strategies were based on exercising and employee assistance programmes.
A research report submitted in fulfillment of the requirements for the Master of Arts in Social Work, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; COVID-19 pandemic; coping strategies; Department of Social Development; experiences; social work; workplace stress; workload; wellbeing; SDG-8: Decent work and economic growth